ANALYSIS OF FACTORS INFLUENCING PATIENT'S SATISFACTION TOWARD ACUPUNCTURE THERAPY IN GRIYA AKUPUNTUR SIDOREJO PARE REGENCY OF KEDIRI - Ardhaenu, Kartika Fahmawati; Puspitasari, Yenny; Dwianggimawati, Mayta Sari (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2019)
Patient satisfaction is a measure of acupuncture quality service which is influenced by various factors. Some factors that influence  patient’s satisfaction that is Performance, Reliability, and Aesthetics. The purpose of this research was to analyze and find out the factors influencing patient’s satisfaction toward acupuncture therapy in “Griya Akupuntur” Sidorejo,Pare, Regency of Kediri. This research used observational with crossectional approach as the design research. The sampling of the research was purposive sampling which is obtained 45 of the respondents as samples. Instrument in this research was questionnaire. Data processing used ordinal regressonand ordinal multiple regressonstatistical tests with Coefficient(α) = 0.05.The result showed that Performance influence patient's satisfaction  in the sufficient category, 20 respondents (44.4%).Reliability also influenced patient’s satisfaction in sufficient category, 20 respondents (44.4%). While, Aesthetic influenced patient’s satisfaction in sufficient category, 19 respondents (42.2%). The test results of  analysis Ordinal regressionand  patient’s satisfaction factor were Performance (0.01), Reliabiliy (0.011), and aesthetics (0.075). Also, test results of ordinal multiple regression were Performance (0.001), Reliabiliy (0.123), and aesthetics (0.551). Then, from the results can be concluded that the most influential factor towards patient's satisfaction  is Performance which  has value of Sig 0.001 < (α = 0.05), it means that  H0 is rejected and  H1 is accepted. Factors that influence  patient’s satisfaction in acupuncture therapy consist of Performance, Reliability and Aesthetic.  All of the three factors are very influential the patient’s satisfaction assessment in acupuncture therapy. Some facilities are needed to be attempted, such as improving lobby, expanding parking area and giving suggestion box in Griya Acupuncture. Factors that influence  patient’s satisfaction in acupuncture therapy consist of Performance, Reliability and Aesthetic.  All of the three factors are very influential the patient’s satisfaction assessment in acupuncture therapy. Some facilities are needed to be attempted, such as improving lobby, expanding parking area and giving suggestion box in Griya Acupuncture.